The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1678-4766e2017010
|View full text |Cite
|
Sign up to set email alerts
|

A geometric morphometric study of sex differences in the scapula, humerus and ulna of Chaetophractus villosus (Xenarthra, Dasypodidae)

Abstract: ABSTRACT. Sexual diff erences in some of the components of the pectoral girdle and forelimb of Chaetophractus villosus (Desmarest, 1804) were investigated by means of geometric morphometrics. A total of 15 scapulae (7 males, 8 females) and 50 humeri-ulnae complexes (24 males, 26 females) were examined. No size diff erences were detected between sexes for any of the bones, but shape diff erences were found for the humerus and the ulna that enhance the in-forces or the related in-levers. Females had a more robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A similar protuberance, but even more developed than in bathyergids has been observed in armadillos, e.g. Chaetophractus villosus and Zaedyus pichiy (Acuña et al, 2017;Marshall et al, 2021). On the medial side of the scapula, the subscapular fossa is relatively flat and similar among all four species.…”
Section: Extrinsic Musclessupporting
confidence: 73%
“…A similar protuberance, but even more developed than in bathyergids has been observed in armadillos, e.g. Chaetophractus villosus and Zaedyus pichiy (Acuña et al, 2017;Marshall et al, 2021). On the medial side of the scapula, the subscapular fossa is relatively flat and similar among all four species.…”
Section: Extrinsic Musclessupporting
confidence: 73%
“…However, these are different to Tamandua, because this surface is not so great as to give origin to the m. subscapular, similar to what occurs in armadillos, where it is observed that this surface is wide but only at the level of the caudal angle (Acuña, Sidorkewicj, Popp, & Casanave, 2017;Miles, 1941;Olson, Womble, Thomas, Glenn, & Butcher, 2016;Taylor, 1978), which is considered by Monteiro and Abe (1999) as an expansion of the infraspinous fossa in armadillos and developed due to the greater retraction required by the thoracic limb in order to dig-where a major part of the force is contributed by the m. teres major for their fossorial habits (Olson et al, 2016).…”
Section: Comparative Anatomymentioning
confidence: 77%
“…Even in non‐human primates, this surface has already been previously described (Mivart, ), and current studies have indicated its presence such as in Lemur catta (Makungu, Groenewald, Plessis, Barrows, & Koeppel, ), cercopithecids (Dunham, Kane, & McGraw, ) and Saguinus leucopus (Vélez‐García, Monroy‐Cendales, & Castañeda‐Herrera, ). However, these are different to Tamandua, because this surface is not so great as to give origin to the m. subscapular, similar to what occurs in armadillos, where it is observed that this surface is wide but only at the level of the caudal angle (Acuña, Sidorkewicj, Popp, & Casanave, ; Miles, ; Olson, Womble, Thomas, Glenn, & Butcher, ; Taylor, ), which is considered by Monteiro and Abe () as an expansion of the infraspinous fossa in armadillos and developed due to the greater retraction required by the thoracic limb in order to dig—where a major part of the force is contributed by the m. teres major for their fossorial habits (Olson et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…Geometric morphometric analyses on armadillo species have shown that adaptations to digging ability seem to be mostly related to a more secure elbow joint and more powerful muscles that control the forearm and hand (Milne et al, 2009 ). The ulna is one of the main bones undergoing stress during burrowing (Acuña et al, 2016 ). Moreover, digging ability has been previously shown to be well characterized by the relative length of the olecranon of the ulna, in other burrowing mammals such as armadillos (Vizcaíno et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%